2022
DOI: 10.33265/polar.v41.7773
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean spatial trends from 2005 to 2019 in Svalbard, Norway

Abstract: This study uses cetacean sighting data, acquired via a citizen science programme, to update distributions and spatial trends of whales and dolphins in waters around the Svalbard Archipelago during the period 2005–2019. Distributions, based on kernel density estimates, from an early period (2005–2019) and a recent period (2015–19) were compared to identify potential shifts in distribution in this area, which is experiencing rapid warming and concomitant sea-ice losses. Among the three Arctic endemic cetaceans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…At Isfjorden, the overall occurrence rate, while much lower than at Eastern Fram Strait, was still higher than expected. Previous studies have reported some sightings around the mouth of this fjord 16 , 17 , 19 , but in general sperm whales are not common in the area. Sperm whales are known to avoid ice-covered areas 6 , 11 , 35 and these two locations had the lowest overall ice cover of the eight sites during the deployment periods (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…At Isfjorden, the overall occurrence rate, while much lower than at Eastern Fram Strait, was still higher than expected. Previous studies have reported some sightings around the mouth of this fjord 16 , 17 , 19 , but in general sperm whales are not common in the area. Sperm whales are known to avoid ice-covered areas 6 , 11 , 35 and these two locations had the lowest overall ice cover of the eight sites during the deployment periods (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The Eastern Fram Strait location had the highest sperm whale occurrence in our study. While a visual survey from 1995 to 2001 did not report sperm whale sightings in the Eastern Fram Strait 42 , more recent studies from the same area do report their presence 14 , 16 , 17 , 19 . At Isfjorden, the overall occurrence rate, while much lower than at Eastern Fram Strait, was still higher than expected.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Twenty-one stocks are currently recognized (Hobbs et al 2019); one of these resides around Svalbard, Norway. This is one of the smallest stocks, which was recently estimated to number 549 individuals (95% confidence interval: 436−723; Vacquie-Garcia et al 2020), although white whales are the most commonly observed cetacean in Svalbard (Storrie et al 2018;Bengtsson et al 2022). Reasons for this seeming discrepancy include the fact that white whales are easy to spot and spend most of their time in the summers in coastal waters off the west coast of Svalbard, where their distribution overlaps with people (Vacquie-Garcia et al 2018).…”
Section: Introductionmentioning
confidence: 99%